Investigation of Rational and Intuitive Decision-Making Styles and Sportsmanship Behaviours of Student Athletes Participating in Inter-university Handball Competitions - Ahmet Yılmaz ALBAYRAK; Mustafa Barış SOMOĞLU; Mine KOÇ; Mustafa KOÇ (Sportif Bakış Spor ve Eğitim Bilimleri Dergisi)
The principal objective of this study is to ascertain the extent to which athletes engage in rational and intuitive decision-making processes and exhibit sportsmanship behaviors, to elucidate the interrelationship between these two constructs, and to examine them in light of the identified variables. To this end, a total of 144 participants (78 female, 54.2%; 66 male, 45.8%) engaged in handball at the university level constituted the study group. The study group was selected using the convenient sampling method. The research was conducted using the cross-sectional scanning method in a quantitative approach. The "Rational and Intuitive Decision Making Styles Scale," the "Sportsmanship Behavior Scale," and the "Personal Information Form," which were created by the researcher, were utilized in the study. The data were analyzed using descriptive statistics, a T-test for dependent groups, a one-way ANOVA, correlation, and regression tests. The applicability of the analyses was determined by considering the values of kurtosis and skewness. The findings indicated that the rational and intuitive decision-making styles and sportsmanship behaviors exhibited by the handball athletes who participated in the research were above the average level. Upon examination of the differences between the rational and intuitive decision-making scale and the independent variables, significant differences were identified with regard to gender, academic department, university, purpose of participation in sports, and income perception. The findings obtained from the independent variables in terms of sportsmanship behaviors revealed significant differences with regard to gender, age, and the purpose of engaging in sports, whereas sportsmanship behaviors exhibited similarities with respect to the number of years spent participating in sports and the academic department. Another noteworthy finding is that there is a positive, albeit moderately significant, correlation between rational and intuitive decision-making styles and sportsmanship behaviors (r = 0.627). Furthermore, the rational and intuitive decision-making styles of athletes serve as a valuable predictor of sportsmanship behaviors (39%).